Pengaruh Pengetahuan, Kepercayaan dan Religiusitas Terhadap Kepatuhan Orang Pribadi Membayar Pajak dengan Membayar Zakat Sebagai Variabel Moderasi Di KPP Pratama Cimahi - Binekas, Bani; Rahmah, Nunung Aini; Krismawati, Ratih Ginanjar (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine and analyze whether Knowledge, Trust, and Religiosity influence Individual Tax Compliance with Zakat Payment as a Moderating Variable. A case study was conducted on Individual Taxpayers registered at the KPP Pratama Cimahi Tax Office. A total of 400 respondents were sampled. This study uses validity and reliability tests, as well as statistical tests with a multiple regression analysis approach and Moderate Regression Analysis (MRA). The research results show that (1) Knowledge is in the very good category with a score percentage of 91%. (2) Trust is in the very good category with a score percentage of 89%. (3) Religiosity is in the very good category with a score percentage of 91%. (4) Knowledge has a positive and significant effect on individual tax compliance; Trust has a positive and significant effect on individual tax compliance; Religiosity has a positive and significant effect on individual tax compliance; Knowledge, Trust, and Religiosity simultaneously have a positive and significant effect on individual tax compliance. (5) Knowledge, Trust, and Religiosity with Zakat Payment as a Moderating Variable simultaneously have a significant effect on individual tax compliance.